2021
DOI: 10.1080/13685538.2021.1948992
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and tolerability of ultra-hypofractionated radiotherapy in low-intermediate risk prostate cancer patients: single center experience

Abstract: Background: We aimed to investigate the efficacy and tolerability of ultra-hypofractionated radiotherapy (UHRT) in the treatment of low and intermediate-risk prostate cancer patients. Methods: This retrospective study was conducted using data derived from 44 patients who underwent UHRT, and toxicity assessment and clinical response were investigated. Treatment consisted of 35-36.25 Gy in 5 fractions using stereotactic ablative radiotherapy (SABR) with the Linac-based delivery system. Results: The median durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Regarding acute GU toxicity, our study detected prostate volume as a risk factor. Dincer et al likewise reported PTV as a risk factor for acute GU toxicity [6]. In addition, Wang et al reported baseline urinary quality of life (QOL) as a risk factor for acute urinary incontinence [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding acute GU toxicity, our study detected prostate volume as a risk factor. Dincer et al likewise reported PTV as a risk factor for acute GU toxicity [6]. In addition, Wang et al reported baseline urinary quality of life (QOL) as a risk factor for acute urinary incontinence [9].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to GI toxicity, GU toxicity was more frequent. Table 4 shows previous reports regarding the relationships between toxicities and risk factors [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In addition, compared to the IMRT, the SBRT has similar toxicity profiles, like the National Comprehensive Cancer Network (NCCN) guidelines suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate hypofractionation should therefore be considered for those patient who are younger and who might experience long terms effects 13 . More studies are now investigating the tolerability of ultra-hypofractionated radiotherapy in an attempt to improve the therapeutic gain in the management of cancer suggesting that these approaches are well-tolerated and showed no statistical difference in toxicity 14 .…”
mentioning
confidence: 99%